The beans of Egypt, Maine : the finished version - Chute, Carolyn (San Diego : Harcourt Brace, 1995)
Earlene marries into the povertystricken Bean family and finds herself being pulled down into their destitution of resources and spirit. In spite of everything, Earlene chooses to become her own woman.
Notable/Best Books (A.L.A.).
Wilson's Fiction.
Young Adult
Keywords: Family -- Maine -- Fiction; Family life -- Fiction; Poor -- Maine -- Fiction; Maine -- Fiction; Domestic fiction